THE DEVELOPMENT OF PRAGMATICS AND PRAGMATIC ANALYSIS IN ENGLISH LANGUAGE - Akhmedov, O.S; Normetova, Munira (Educational Research in Universal Sciences, 2022)
In this article the author investigates about the development of pragmatics as an independent branch of linguistics, importance and number of issues raised, main conceptions and principles. Since language is studied more deeply, the abstract meaning which is not shown in form is began to be understood and analyze what speaker is willing to say and listener can understand. The author provides a brief and clear information about pragmatics and its explanations.